Determination of the presence of metabolic syndrome in patients of erectile dysfunction and assess correlation of its components with erectile dysfunction in a tertiary care hospital in central India - Sharma, Vivek; Tripathi, Vishwadeepak; Shukla, Pushpendra K.; Tripathi, Sunil K. (International Journal of Research in Medical Sciences, 2021)
Background: Erectile dysfunction (ED) is a common medical condition that affects approximately 100 million men worldwide and is currently recognized as a major public health problem. Metabolic syndrome (Met S) is a complex entity consisting of multiple interrelated factors including insulin resistance, central adiposity, dyslipidaemia, endothelial dysfunction and atherosclerotic disease, low-grade inflammation, and in males, low testosterone levels. we aimed to investigate the relationship between metabolic syndrome and ED presence and severity. Methods: Patient who came to urology OPD with c/o of ED and were evaluated for it with physical examination, questionnaire, investigations>after confirmation of ED were evaluated for presence of metabolic syndrome and its individual components Results: Out of these 202 patients, 98 patients were found to have metabolic syndrome. The mean age of participating patients in this study was 47.2±5.6 years. Metabolic syndrome was diagnosed in 98 (34.78%) of 202 patients. Statistically significant association was found between ED and metabolic syndrome, waist circumference and fasting blood glucose (p<0.001 with each parameter). We also found a significant correlation between hypertension and ED but no significant correlation with triglyceride levels or HDL levels. Conclusions: ED is strongly associated with metabolic syndrome and the efforts for treatment of erectile dysfunction must be made in the context of metabolic syndrome and its constituents with a low threshold to diagnose the cardiovascular disease.